2021
DOI: 10.1039/d1ra02155a
|View full text |Cite
|
Sign up to set email alerts
|

Flexible electric-double-layer thin film transistors based on a vertical InGaZnO4 channel

Abstract: Flexible electric-double-layer (EDL) thin film transistors (TFTs) based on a vertical InGaZnO4 (IGZO) channel are fabricated at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Several flexible materials have been explored as substrates ( Figure ) including PI, [ 41 ] Polyethylene Terephthalate (PET), [ 42 ] Polyethylene Naphthalate (PEN), [ 43 ] Thermoplastic Polyurethane (TPU), [ 44 ] cellulose paper, [ 45 ] Polyestersulfone (PES), [ 46 ] and Colorless Polyimide (CPI), [ 47 ] whereas their properties are exposed in Table 1. PI is a widely commercialized polymer and due to its attractive properties [ 44 ] and it is the most popular substrate for both TFTs and memristive applications, as noted in Tables S3 and S5 (Supporting Information).…”
Section: Flexible Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several flexible materials have been explored as substrates ( Figure ) including PI, [ 41 ] Polyethylene Terephthalate (PET), [ 42 ] Polyethylene Naphthalate (PEN), [ 43 ] Thermoplastic Polyurethane (TPU), [ 44 ] cellulose paper, [ 45 ] Polyestersulfone (PES), [ 46 ] and Colorless Polyimide (CPI), [ 47 ] whereas their properties are exposed in Table 1. PI is a widely commercialized polymer and due to its attractive properties [ 44 ] and it is the most popular substrate for both TFTs and memristive applications, as noted in Tables S3 and S5 (Supporting Information).…”
Section: Flexible Substratesmentioning
confidence: 99%
“…In particular, vertical TFTs (VTFTs) can improve the bending capabilities due to higher resilience to in‐plane cracking of the active semiconductor. [ 1 ] Also, recent studies on VTFTs successfully demonstrated low operating voltages, as low as 0.1 V, and small SS (≈80 mV dec −1 ) [ 45 ] that is ideal for low‐power and portable electronics.…”
Section: Flexible Electronic Devicesmentioning
confidence: 99%